2014
DOI: 10.4103/0974-2077.150743
|View full text |Cite
|
Sign up to set email alerts
|

Study of platelet-rich plasma injections in the treatment of androgenetic alopecia through an one-year period

Abstract: Background:Platelet-rich plasma (PRP) is defined as an autologous concentration of plasma with a greater count of platelets than that of whole blood. Its action depends on the released growth factors from platelets. It has been investigated and used in numerous fields of medicine. Recently, PRP has received growing attention as a potential therapeutic tool for hair loss.Aims:To evaluate the efficacy and safety of PRP injections in the scalp of patients with androgenetic alopecia.Settings and Design:Prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
193
6
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(209 citation statements)
references
References 20 publications
7
193
6
3
Order By: Relevance
“…Various studies in the literature indicated that PRP stimulates a number of active features such as growth rate, hair count, hair density, hair shaft diameter, hair root strength, anagen hair, telogen hair, terminal hair density, epidermal keratinocytes, hair follicular bulge cells, and lead to increase in small blood vessels in hair follicle, prevents dermal papilla apoptosis, extent anagen phase, and enhances hair regrowth [70][71][72][73][74]. The carrier which contains dalteparin/protamine micro particles (DP MP) (low-molecular-weight heparin) was used to enhance the efficiency of PRP.…”
Section: The Mechanism Of Platelet-rich Plasma In Androgenetic Alopeciamentioning
confidence: 99%
“…Various studies in the literature indicated that PRP stimulates a number of active features such as growth rate, hair count, hair density, hair shaft diameter, hair root strength, anagen hair, telogen hair, terminal hair density, epidermal keratinocytes, hair follicular bulge cells, and lead to increase in small blood vessels in hair follicle, prevents dermal papilla apoptosis, extent anagen phase, and enhances hair regrowth [70][71][72][73][74]. The carrier which contains dalteparin/protamine micro particles (DP MP) (low-molecular-weight heparin) was used to enhance the efficiency of PRP.…”
Section: The Mechanism Of Platelet-rich Plasma In Androgenetic Alopeciamentioning
confidence: 99%
“…The positive effect of PRP in the treatment of AGA has been documented in other studies. [11,12,13].Mechanisms of hair regrowth induced by skin needling include: [14,15,16] release of platelet derived growth factor, epidermal growth factors through platelet activation and skin wound regeneration mechanism; activation of stem cells in the hair bulge area; overexpression of hair growth related genes vascular endothelial growth factor, B catenin, Wnt3a, and Wnt10 b. A 12-week study by Dhurat et al [17] showed that dermaroller along with Minoxidil treated group was statistically superior to Minoxidil treated group in promoting hair growth in men with AGA.…”
Section: Discussionmentioning
confidence: 99%
“…[8,10] It also appears to increase the perifollicular vascular plexus through the increase of VEGF and PDGF levels, which have angiogenic potential. [11] Uebel et al [5] showed that pretreatment of follicular units with PRP before transplantation resulted in improved hair growth and density. The positive effect of PRP in the treatment of AGA has been documented in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These studies include Anitua et al [29], Puig et al [30], Mapar et al [31], Gupta et al [32], and Alves and Grimalt [33]. Studies from 2015 (Singhal et al [12] and Gentile et al [34]), 2014 (Gkini et al [27], Khatu et al [35], Schiavone et al [36], and Cervelli et al [28]), and 2011 (Takikawa et al [37]) are also compared. …”
Section: Methodsmentioning
confidence: 99%
“…Growth factors in PRP promote hair regrowth by binding to their respective receptors expressed by stem cells of the hair follicle bulge region and associated tissues. Upon ligand binding, stem cells induce the proliferative phase of the hair follicle, producing the anagen follicular unit and facilitating hair regrowth [27,25]. Further, they activate downstream cascades leading to angiogenesis and stimulation and generation of adnexal structures.…”
Section: Introductionmentioning
confidence: 99%